Kid Scanlan - Witwer, H. C. (Harry Charles), 1890-1929 (Salt Lake City, UT : Project Gutenberg, 2009)
"Kid Scanlan" by H. C. Witwer is a novel written in the early 20th century. The story centers around the titular character, Kid Scanlan, a welterweight boxer whose journey from the ring to becoming a movie star unfolds with humorous and colorful anecdotes. Through a blend of wit and adventure, the novel captures the highs and lows of Scanlan's life as he navigates fame, fortune, and the challenges that come with them. The opening of "Kid Scanlan" introduces readers to the Kid as he reflects on his boxing career and his path to championship glory. It details the aftermath of his thrilling bout against One-Punch Ross, leading to a surprise transition into the film industry. Supported by his savvy manager, Johnny Green, Scanlan embarks on a new adventure in Hollywood, marked by a series of comedic misadventures involving film producers, eccentric directors, and a host of misunderstandings. As Scanlan prepares to play the lead in his own movie, the narrative sets the stage for a delightful exploration of showbiz alongside the chaos of Scanlan's boxing days. (This is an automatically generated summary.)
Release date is 2009-08-22
Produced by Al Haines
Keywords: Humorous stories; Motion picture industry -- Fiction; Boxers (Sports) -- Fiction